The importance of marketing for micro and small enterprises (Research, Society and Development, 2023)
The MSME business marketing process includes two main aspects, such as networking and word of mouth communication. Networking for business activities means that companies come together with a common goal, working together and cooperating by sharing ideas, knowledge, resources and technology. In this way, the present work has as main objective to demonstrate the importance of marketing for the success of a company and to identify the main difficulties faced by entrepreneurs. Therefore, it is expected to answer the problem question of “How can marketing help in the success of micro and small companies?”, through a bibliographical review of a qualitative documental nature. The marketing function in SMEs is hampered by constraints such as insufficient cash flow, lack of marketing expertise, business size, tactical customer-related issues, and strategic customer-related issues. Small businesses need marketing in a format that is compatible with small business characteristics and acceptable to the small business owner/manager. The results of the study generate a general picture of an unfavorable position of SMEs, especially in the area of insufficient information, bad marketing activities constituted mainly by sales, neglecting the other elements of the marketing mix. Many authors have stated that a market-oriented business approach will result in better corporate performance and many studies have found a positive association between market orientation and performance.